Associations between coping and marijuana use in a nationally representative sample of adolescents in the United States. (May 2018) - Lee-Winn, Angela E.; Mendelson, Tamar; Johnson, Renee M.
Abstract: Maladaptive coping strategies have been linked with substance use. Little is known, however, about associations between coping and marijuana use in the general U.S. adolescents. We used nationally representative data to examine associations between coping and marijuana use among U.S. adolescents. We hypothesized that marijuana use would be positively associated with both avoidance and distraction coping and negatively associated with problem solving. We calculated adjusted prevalence ratios and odds ratios to assess associations of three coping styles (avoidance, distraction, problem solving) and six coping profiles based on combinations of the styles (adaptive, low on all styles, distracted, high on all styles, avoidant, maladaptive) with lifetime marijuana use and past 12-month frequency of use using data from the National Comorbidity Survey: Adolescent Supplement ( n  = 8476, ages 14–18 years). Avoidance and distraction coping were positively and problem solving was negatively associated with lifetime marijuana use. Avoidance coping was positively associated, and problem solving negatively associated, with past 12-month frequency of use. Compared to the adaptive coping profile (low avoidance and distraction, high problem solving), maladaptive profile (high avoidance and distraction, low problem solving) and avoidance profile (high avoidance, low distraction and problem solving) were each positively associated with lifetime marijuana use and past 12-month frequency of use. Avoidance coping, especially in combination with limited problem solving, was positively associated with lifetime marijuana use and past 12-month frequency of use. Our findings have potential to inform interventions for reducing adolescent marijuana use. Highlights: Avoidance coping was associated with higher lifetime and frequency of marijuana use. Distraction coping was associated with higher lifetime marijuana use. Problem solving was associated with lower lifetime and frequency of marijuana use. Avoidance coping combined with low problem solving appeared to be especially maladaptive.